Seeking a place in a nation: the exodus of the Tunisian Jewish population 1954-1967 - Haley, Sean (AUC Knowledge Fountain, 2012)
In the eleven years after the independence and creation of the Republic of Tunisia, the population of the Jewish community declined by approximately 88.7% because of emigration to France, Israel, and other countries. This period, as will be shown, was critical in shaping the ethno-religious arrangement of peoples in Tunisia today. This occurred because a centralizing newly-independent state created a nation through identity based upon citizenship. Tunisia is a particularly good case study of homogenizing post-colonial nation-states because the government never sought to exclude any part of the population through direct action. Instead, domestic and international events that shook the nation and had an impact on the Jewish minority, such as independence, the reorganization of the Jewish community of 1958, the 1961 Bizerte Crisis and the Six Day War, made a solution such as exile palatable for the Jews.